Effect of H. pylori presence on the severity of Crimean Congo hemorrhagic fever - Dökmetaş, İlyas; Yönem, Özlem; Dökmetaş, Sebila; Özdemir, Levent; Kılıçlı, Fatih; Engin, Aynur; Büyükhan, İbrahim (My University, 2014)
Background and Aims: Crimean Congo hemorrhagic fever can cause a fa- tal hemorrhagic syndrome. We aimed to investigate whether the presence of Helicobacter pylori increases the bleeding or severity of Crimean Congo hemorrhagic fever. Materials and Methods: Forty-two patients with Crime- an Congo hemorrhagic fever who had dyspepsia and were hospitalized be- tween April 2009 and July 2009 were included in the study. The patients were divided into two groups according to their fecal Helicobacter pylori an- tigen positivity. Clinical and laboratory severity criteria for Crimean Congo hemorrhagic fever were investigated in both groups. Results: We could not find any difference between the two groups with regard to severity as de- fined by clinical and laboratory criteria. Conclusion: This is the first study in the literature investigating the role of Helicobacter pylori in the severity of Crimean Congo hemorrhagic fever from a country in which both Crimean Congo hemorrhagic fever and Helicobacter pylori are endemic. Further stud- ies including a larger number of Crimean Congo hemorrhagic fever patients are necessary to recommend Helicobacter pylori screening and eradication in Crimean Congo hemorrhagic fever.

Giriş ve Amaç: Kırım Kongo kanamalı ateşi ölümcül hemorajik bir sendro- ma neden olabilir. Bu çalışmada Helicobacter pylori varlığının Kırım Kongo kanamalı ateşi hastalığının şiddeti ya da kanama üzerine etkisinin olup olma- dığını araştırdık. Gereç ve Yöntem: Kırım Kongo kanamalı ateşi nedeniyle Nisan 2009-Temmuz 2009 arası hospitalize edilen kırk iki dispeptik hasta çalışmaya dahil edildi. Hastalar fekal Helicobacter pylori antijeni pozitifliği durumuna göre iki gruba ayrıldı. Her iki grupta Kırım Kongo kanamalı ate- şi'nin klinik ve labaratuvar olarak şiddet kriterleri değerlendirildi. Bulgular: Klinik ve laboratuvar kriterleri açısından iki grup arasında Kırım Kongo ka- namalı ateşi hastalık şiddeti açısından farklılık saptanmadı. Sonuç: Bu çalış- ma Helicobacter pylori'nin Kırım Kongo kanamalı ateşi'nin şiddeti üzerine etkisini araştıran ilk çalışma olması ve hem Helicobacter pylori hem de Kırım Kongo kanamalı ateşi'nin endemik olduğu bir bölgeden yapılması nedeniyle önemlidir. Ancak Kırım Kongo kanamalı ateşi hastalarında rutin Helicobac- ter pylori taranması ve eradikasyonunun önerilebilmesi için daha geniş vaka sayılı çalışmalara ihtiyaç vardır.
Kırım Kongo kanamalı ateşine H. pylori varlığının etkisi
Keywords: Crimean Congo Hemorrhagic Fever; Helicobacter Pylori; Severity; Kırım Kongo Kanamalı Ateşi; Helicobacter Pylori; Şiddet